2009
DOI: 10.1111/j.1432-2277.2008.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon-α-based treatment for chronic hepatitis C in renal transplant recipients: an open pilot study

Abstract: Summary Treatment of hepatitis C in renal transplant recipients remains a controversial issue, as interferon therapy has been associated with a high risk of rejection and poor efficacy. We report here the use of pegylated interferon‐α, alone or in combination with ribavirin, in renal transplant recipients with chronic hepatitis C. Eight renal transplant recipients with chronic hepatitis C were recruited. The mean delay between renal transplantation and antiviral therapy was 198.8 months. Sustained virological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…35 Another study showed that administration of pegylated interferon plus ribavirin resulted in 97% of patients exhibiting a sustained viro logic response. 36 Patients with ESRD exhibit a poor toler ance to ribavirin and therefore this treatment regimen is difficult for those on dialysis. A metaanalysis of 287 patients treated with pegylated interferon plus riba virin, however, identified a sustained virologic response in 60% of patients.…”
Section: Management and Treatment Of Patients With Hcvmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Another study showed that administration of pegylated interferon plus ribavirin resulted in 97% of patients exhibiting a sustained viro logic response. 36 Patients with ESRD exhibit a poor toler ance to ribavirin and therefore this treatment regimen is difficult for those on dialysis. A metaanalysis of 287 patients treated with pegylated interferon plus riba virin, however, identified a sustained virologic response in 60% of patients.…”
Section: Management and Treatment Of Patients With Hcvmentioning
confidence: 99%
“…Second, many of the included studies used pegylated interferon, which exhibits a longer halflife than either recombinant or interferonα. 36,[43][44][45][46][47] Graft dysfunction is the most frequent adverse effect of antiviral therapy and results in an interruption of treat ment. Graft dysfunction has been reported to occur in ~51% of patients, 41 although this rate is reportedly lower (12.5%) in some other case series.…”
Section: Management and Treatment Of Patients With Hcvmentioning
confidence: 99%
“…IFNa is associated with an increased risk for allograft dysfunction and rejection, making post-transplant treatment more difficult. Consequently, HCV-infected kidney transplant recipients should be treated (in conjunction with hepatology or infectious disease experts) only if the benefits outweigh the risk for rejection (61). The effect of immunosuppression on the progression of HCV-related liver injury and survival remains uncertain, although in general more intensive immunosuppression (including the use of OKT3 and antithymocyte globulin) has been associated with increased liver disease.…”
Section: Hcv Infectionmentioning
confidence: 99%
“…Using data from two meta-analyses published in 2008 (Table 1) [45,46], Casanovas [47] found an overall SVR of 40% with a summary drop-out rate of 19%. Other recent observational studies demonstrate the wide variation in practice that makes such meta-analyses difficult [48][49][50][51][52][53][54][55][56][57]. Based on current data, PEG-interferon does not appear to be superior to standard interferon in treating chronic HCV infection in those on dialysis.…”
Section: Treatment Of Hcv In Esrd Patientsmentioning
confidence: 74%